2016
DOI: 10.1080/15583724.2015.1136641
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Applications for Electrospun Fibers

Abstract: Electrospinning is a versatile technique providing highly tunable nanofibrous nonwovens. Many biomedical applications have been developed for nanofibers, among which the production of antimicrobial mats stands out. The production of scaffolds for tissue engineering, fibers for controlled drug release, or active wound dressings are active fields of research exploiting the possibilities offered by electrospun materials. The fabrication of materials for active food packaging or membranes for environmental applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 158 publications
0
37
0
Order By: Relevance
“…However, PCL as the matrix has limited applicability in biomedical practices because it cannot solely used to regenerate bone tissues due to the minimal stiffness, hydrophobicity and marginal bioactivity. Nonetheless, the use of bioactive materials together with PCL for the preparation of the electrospun mats has received great attention for novel development of membranes with superb cell proliferation and wound dressing [31][32][33][34]. For example, Correia and co-workers [35] investigated the use of extracted aloe vera chitosan nanofibrous materials and the subsequent fabrication using electrospinning method in the application of skin recovery and wound healing.…”
Section: Electrospun Nanoparticlesmentioning
confidence: 99%
“…However, PCL as the matrix has limited applicability in biomedical practices because it cannot solely used to regenerate bone tissues due to the minimal stiffness, hydrophobicity and marginal bioactivity. Nonetheless, the use of bioactive materials together with PCL for the preparation of the electrospun mats has received great attention for novel development of membranes with superb cell proliferation and wound dressing [31][32][33][34]. For example, Correia and co-workers [35] investigated the use of extracted aloe vera chitosan nanofibrous materials and the subsequent fabrication using electrospinning method in the application of skin recovery and wound healing.…”
Section: Electrospun Nanoparticlesmentioning
confidence: 99%
“…23 Due to these unique properties electrospun bres have been proposed for uses in several biomedical applications including scaffolds for tissue engineering, medical implants, biosensors, and wound dressings. 24,25 The functionalization of electrospun dressings with active substances has recently become an active research topic. Electrospun brous scaffolds benet from their inherently small pores to inhibit microbial invasions and to control uid drainage.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that chitosan (CS) has wide application in biomedical and pharmacology because of its non-toxicity and unique biological and physiochemical properties as well as antimicrobial activity. Indeed, linoleic acid (LA) comprised of Trans-11 and Cis-9 is one of the appropriate acids that inhibits fungal cell growth (26,27).…”
Section: Discussionmentioning
confidence: 99%